دور الائتمـان المصـرفـي في تمـويل المشـروعات الصغيـرة والمتوسـطة في سـورية - محمود, يوسف; عباس, غادة; قبرصلي, صبا (Tishreen University Journal- Economic and Legal Sciences Series, 2013)
تعدّ المشروعات الصغيرة والمتوسطة دعامة أساسية في الاقتصاد الوطني، قد باتت الحاجة ملحة لتطوير وتحفيز هذا النوع من المشروعات لا سيما بعد أن أثبتت التجارب الدولية الدور الكبير لمثل هذا المشروعات في تحفيز النمو الاقتصادي ودعم عملية التنمية والحد من البطالة. يناقش هذا البحث أهم المشكلات التي تواجه تمويل المشروعات الصغيرة والمتوسطة، ولاشك أن المؤسسات المالية بعامة والمصارف بخاصة تلعب دوراً في تمويل ودعم هذه المشروعات، وعلى الرغم من ذلك فإن أصحاب هذه المشروعات يعانون من صعوبات كبيرة في الحصول على مصادر التمويل، لاسيما الائتمان المصرفي، ويعود ذلك لأسباب عديدة في مقدمتها تشدد المصارف في منح التمويل اللازم لهذه المشروعات بسبب ضعف الضمانات المتاحة لديها. ولقياس درجة إسهام المصارف في تمويل هذه المشروعات قامت الباحثة بتصميم استبانة وزعت على عدد من المصارف العاملة في سورية، وبعد تحليل إجابات المستقصى منهم واختبار الفرضيات توصلت الباحثة إلى أنّ المصارف لا تقوم بتقديم تسهيلات للقروض الممنوحة للمشروعات الصغيرة والمتوسطة، غير أنهّا تعتمد في قرار تمويلها على السمات الخاصة للمشروع. Small and medium enterprises are considered a basic pillar in the national economy, and there has been a dire need to develop and motivate such enterprises, especially after the international experience has proved the huge role of such enterprises in upgrading the economic growth, supporting the development process and limiting unemployment . This research deals with the most important problems that financing small and medium enterprises faces. It is of no doubt that the financial institutions in general and banks in particular play a role in financing and supporting such enterprises in spite of the big difficulties that their owners face for having the financial resources, including the bank credit. This is due to several reasons, the most important of which is the rigid measures the banks take to grant the needed financing for those enterprises because of the weak guarantee. The researcher conducted such a study for measuring the role of banks in financing these enterprises by designing a questionnaire distributed to a number of banks working in Syria, and upon making the analysis on that survey and testing the suppositions, the researcher concluded that Syria's working banks have no facilities for small and medium enterprises granted loans, but they depend on the special features of the enterprises to take the financing decision.